2011
DOI: 10.1136/bcr.08.2010.3270
|View full text |Cite
|
Sign up to set email alerts
|

An isolated cardiac metastasis from colorectal adenocarcinoma

Abstract: Epidemiological information relating to cardiac metastases is predominantly based on autopsy studies. The reported incidence ranges from 2.3-18.3%. It is usually found in the presence of widely disseminated disease. Here, a case of an isolated, asymptomatic cardiac metastasis from colonic adenocarcinoma is reported. The metastasis was detected later, following bowel resection and was not amenable to surgical resection. The patient is receiving ongoing care from the oncology team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…We found only 12 cases of well-documented metastatic CRC that involved the right ventricle of the heart. Table I shows 13 reports including the present case (3,6,9,(19)(20)(21). The median age at presentation in these reports was 71 years (range=35-77 years) with a slight prevalence in female patients (seven patients, 53.8%).…”
Section: ) (F) T1-weighted Magnetic Resonance Imaging (Mri) Showing a Slightly High Intense Mass Measuring 20 MM Compared To The Intact Mmentioning
confidence: 86%
“…We found only 12 cases of well-documented metastatic CRC that involved the right ventricle of the heart. Table I shows 13 reports including the present case (3,6,9,(19)(20)(21). The median age at presentation in these reports was 71 years (range=35-77 years) with a slight prevalence in female patients (seven patients, 53.8%).…”
Section: ) (F) T1-weighted Magnetic Resonance Imaging (Mri) Showing a Slightly High Intense Mass Measuring 20 MM Compared To The Intact Mmentioning
confidence: 86%
“…9 Due to their asymptomatic nature, diagnosis and treatment can be challenging. 10 In symptomatic cases, they usually present with heart failure including dyspnoea, tachycardia, and edema. 11 We present a case of colon cancer, and due to suspicion of endocarditis symptoms, echocardiography findings led to the discovery of TV metastasis and SVC involvement.…”
Section: Discussionmentioning
confidence: 99%
“…These metastases account for 1.9% of all metastatic neoplasms 9 . Due to their asymptomatic nature, diagnosis and treatment can be challenging 10 . In symptomatic cases, they usually present with heart failure including dyspnoea, tachycardia, and edema 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The cardiac metastasis mechanism is thought to be as follows: (a) direct extension: Klatt and Heitz [ 23 ] suggested that as the lungs are close to the heart, metastases can reach the heart directly; (b) hematogenous spread: Patel et al [ 24 ] reported the ability of tumor embolization to invade the heart through the portal circulation via the vena cava and liver without seeding into it; and (c) lymphatic spread: Mukai et al [ 2 ] suggested that intralymphatic retrograde metastasis due to mediastinal lymph node metastasis was the major pathway in gastrointestinal cancer.…”
Section: Discussion/conclusionmentioning
confidence: 99%